2018
DOI: 10.53369/neuf4913
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Procedural Justice on Turnover Intention with Mediating Effect of Trust

Abstract: This research conducted a survey to examine the impact of procedural justice on turnover intention through mediation of organizational trust. The study is based on a sample of 141 faculty members of the public and private sector universities of twin cities of Pakistan who completed structured questionnaires for each variable. Data were analyzed using SPSS and results revealed that procedural justice has negative and significant effect on turnover intentions of employees. Furthermore, organizational trust succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In a nutshell, the empirical investigations by Yusoff et al (2021); Yusoff and Yusliza (2020); Ngadiman (2019); Tajammal (2018); Bayarçelik and Findikli (2016); Gharbi et al (2022); Afghan et al (2018); Hussain and Khan (2019); Mengstie (2020) have consistently reported relationships between procedural justice and turnover intention.…”
Section: Literature Review and Hypotheses Development The Relationshi...mentioning
confidence: 96%
“…In a nutshell, the empirical investigations by Yusoff et al (2021); Yusoff and Yusliza (2020); Ngadiman (2019); Tajammal (2018); Bayarçelik and Findikli (2016); Gharbi et al (2022); Afghan et al (2018); Hussain and Khan (2019); Mengstie (2020) have consistently reported relationships between procedural justice and turnover intention.…”
Section: Literature Review and Hypotheses Development The Relationshi...mentioning
confidence: 96%